Immunologic Features of Patients With Advanced Hepatocellular Carcinoma Before and During Sorafenib or Anti-programmed Death-1/Programmed Death-L1 Treatment. Issue 7 (July 2019) - Macek Jilkova, Zuzana; Aspord, Caroline; Kurma, Keerthi; Granon, Anouck; Sengel, Christian; Sturm, Nathalie; Marche, Patrice N.; Decaens, Thomas
Abstract : INTRODUCTION: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide. Today, a promising treatment strategy is focused on the enhancement of antitumor immune responses by immune checkpoint modification. However, as only 20% of patients with HCC are responders, identification of predictive factors is urgently required. Therefore, for the first time, the features of the intrahepatic and circulating immune system in patients with advanced-stage HCC, before and during the treatment, were analyzed. METHODS: We collected fresh HCC biopsies, along with adjacent tumor-free liver tissues and peripheral blood samples, from 21 patients with advanced HCC. Furthermore, we performed an extensive immunomonitoring of patients with HCC treated with sorafenib or programmed death (PD)-1/PD-L1 pathway blockade using multiparametric flow cytometry. RESULTS: We observed that regardless of the treatment, low baseline intratumoral CD4 + /CD8 + T-cell ratio was associated with better overall survival ( P = 0.0002). The baseline frequency of intratumoral PD-1 high CD8 + T cells was significantly lower in patients responding to sorafenib treatment than in the nonresponders ( P = 0.0117), and the frequency of circulating PD-1 high T cells increased with tumor progression ( P = 0.0329). By contrast, responders to PD-1/PD-L1 pathway blockade showed a trend of high baseline frequency of intratumoral PD-1 high CD8 + T cells. Moreover, we observed a trend of LAG3 and TIM3 upregulation on circulating T cells in nonresponding patients to PD-1/PD-L1 pathway blockade. DISCUSSION: Immunosuppressive state, characterized by an enhanced intratumoral CD4 + /CD8 + T-cell ratio, was associated with poor prognosis. Additionally, our results suggest that the frequency of intratumoral PD-1 high CD8 + T cells may serve as a biomarker to identify which individuals will benefit from which treatment and support the use of combination strategies.